Needs of integrated science experiment student worksheet in junior high school to improve students science process skills - G Priscylio; Mulyadi Mulyadi; D Rochintaniawati (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2018)
In this article, we discuss the main arguments that deal with the issue needs ofintegrated science experiment student worksheet in junior high school to improve studentsscience process skills. the very basic issues highlighted in this article is Types of studentworksheet available has not yet guide students to find concepts. The experiment studentworksheet developed by teacher are only confirming the concept. This article is structured asfollows. After giving an overview of the scope of the availability of tools and experimentmaterials in school laboratories, teaching materials used in schools, we review the particularabout the experiment student worksheet can improve students science process skills. Thisresearch is a Descriptive Research. This research was conducted at Junior High School 1 of Pakis Karawang. The data collection used in this research is observation, interview and studentquestionnaire. From this research obtained data that there has been no improvement of studentsscience process skills from practical work conducted using experiment student worksheetdeveloped by teachers. So, we argue that need developed an experiment student worksheet toimprove students science process skills.